Job Crafting and Nurses' Presenteeism: The Effects of Job Embeddedness and Job Irreplaceability - Taotao Liu; Wei Wang; Geyan Shan; Yijie Zhang; Jie Liu; Yongxin Li (Frontiers Media S.A., 2022)
BackgroundPresenteeism is defined as the behavior of people who insist on attending work despite complaints of ill health that should prompt rest and absence from work. Due to the heavy workloads and irreplaceable duties of the nursing service, nurses are a typical representative group suffering from presenteeism. Although more scholars have recently begun focusing on presenteeism, an abundant number of studies have tended to focus on presenteeism's external objective factors. There is, thus, a lack of studies based on variables related to the intra-individual initiative. This study aimed to address this gap by exploring the relationship between job crafting and nurses' presenteeism from the perspective of the individual internal initiative. Furthermore, this study also aimed to examine job embeddedness' mediating effect and job irreplaceability's moderating effect on presenteeism.MethodsA total of 900 nurses from a 3A-graded hospital in Henan Province were invited to participate in the online study in October, November, and December 2021, respectively. Participants were asked to complete Self-report scales on job crafting, job embeddedness, job irreplaceability, and presenteeism at three time points above. Job crafting was measured at Time 1, job embeddedness and job irreplaceability were measured at Time 2, and presenteeism was measured at Time 3.ResultsPresenteeism was significantly associated with differences in participants' age and tenure. Job crafting was significantly positively associated with job embeddedness, and job embeddedness was significantly negatively correlated with presenteeism. Job embeddedness mediated the relationship between job crafting and presenteeism. Job irreplaceability moderated the relationship between job embeddedness and presenteeism.ConclusionsThis study explored job crafting's influence mechanism on nurses' presenteeism, which is beneficial to providing effective suggestions for managing and preventing the incidence of nurses' presenteeism. Future research should consider expanding the sampling area and enriching the occupational fields of included participants to conduct a more in-depth discussion on the relationship between job crafting and nurses' presenteeism.